INTEGRATED MARKETING COMMUNICATIONS DESA WISATA PENGLIPURAN DALAM MENGEMBANGKAN DESTINASI PARIWISATA DI BANGLI - ulio lio; Ulio; I Putu Adi Saskara (UHN IGB Sugriwa Denpasar, 2022)
This research is a qualitative research that examines the Integrated Marketing communications of Penglipuran Tourism Village in an effort to develop International Tourism Destinations in Bangli Regency. This research is important because Penglipuran Tourism Village is one of the traditional villages of Bangli Regency. This village is known as a tourist destination because the people who still carry out and preserve traditional Balinese culture with building architecture and land management still apply the Tri Hita Karana concept, and have succeeded in building tourism that improves the economic life of the people without losing the culture and traditions of the traditional village. Various awards have been won, namely as a tourist village in the World's Top 100 sustainable destinationsin 2019 and winning the title of the cleanest village in the world version of the Bombastic International problem in 2016. The research method used is a qualitative research method. To achieve the research objectives, relevant and adequate data are needed. The technique of determining the informants used a purposive sampling model while the data collection techniques used observations, interviews, documentation and literature studies. The research findings include: The reason for the existence of Penglipuran Village as a tourist village is one of the Bali Aga villages which is unique in terms of physical, ecological, socio-cultural life, and traditions. This uniqueness is the potential to be developed as a tourist attraction. Tourism development in Penglipuran Village is carried out by prioritizing the participation of traditional villages and applying the concept of tourism development policies with a populist dimension. Integrated Marketing Communications used include Direct Marketing, Sales Promotion, Public Relations, Advertising, Sponsorship, and Personal Selling. Furthermore, the communication implications of the integrated marketing communication of Penglipuran tourism village, namely: Cognitive Effect Implications, Affective Effect Implications, and Conative Effect Implications